A Review of the Prospective Effects of Spacing and Varieties on Onion Yield and Yield Components (Allium cepa L.) in Ethiopia - Yohannes Gelaye; Kelemu Nakachew; Solomon Ali (The Scientific World Journal)
Onion (Allium cepa L.) is the most important commercial vegetable crop widely grown throughout the world. It is also an important bulb crop in Ethiopia. However, its production and productivity are restricted by different factors, including biotic and abiotic stresses. This review investigates the potential impacts of spacing and varieties on onion yield and yield components in Ethiopia. Countries around the world are producing onion for its nutritional value, medicinal properties, minerals, proteins, and carbohydrates. In terms of production, onion ranks second only after tomatoes. The average onion yield in Ethiopia is estimated to be 8.8 tons/ha, while in the world, it is approximately 19.7 tons/ha. Inappropriate spacing and inadequate onion varieties are some of the limitations widely described for yield variation in Ethiopia. Thus, to control the size, shape, and yield of onion bulbs, spacing determination and variety improvement are some of the techniques currently employed in Ethiopia. Adama red, Bombay red, and red creole are some of the known varieties in the country, and the intrarow spacings for Adama red and Bombay red are reported to be 4 cm and 6 cm, respectively. Different spacing between onion plants affects how much they produce and other factors such as size and quality, depending on the variety. It is important to assess whether changing spacing makes sense from both a farming and economic standpoint, alongside considering other agricultural methods.